2010
DOI: 10.1002/chem.200902788
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated IrIII Complexes with Substituted 1,10‐Phenanthrolines: A New Class of Efficient Cationic Organometallic Second‐Order NLO Chromophores

Abstract: Cyclometalated cationic Ir(III) complexes with substituted 1,10-phenanthrolines (1,10-phen), such as [Ir(ppy)(2)(5-R-1,10-phen)]Y (ppy=cyclometalated 2-phenylpyridine; R=NO(2), H, Me, NMe(2); Y(-)=PF(6) (-), C(12)H(25)SO(3) (-), I(-)) and [Ir(ppy)(2)(4-R,7-R-1,10-phen)]Y (R=Me, Ph) are characterized by a significant second-order optical non linearity (measured by the electrical field induced second harmonic generation (EFISH) technique). This nonlinearity is controlled by MLCT processes from the cyclometalated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 57 publications
2
54
1
Order By: Relevance
“…Such values are much larger than the one previously obtained for 125a in agreement with an increase in the π-delocalization on the bipyridine ligands induced by the phenyl substituents. A similar observation was previously reported for iridium and ruthenium complexes featuring substituted phenanthroline ligands [148,149].…”
Section: Harmonic Light Scatteringsupporting
confidence: 79%
“…Such values are much larger than the one previously obtained for 125a in agreement with an increase in the π-delocalization on the bipyridine ligands induced by the phenyl substituents. A similar observation was previously reported for iridium and ruthenium complexes featuring substituted phenanthroline ligands [148,149].…”
Section: Harmonic Light Scatteringsupporting
confidence: 79%
“…These data clearly show the large quadratic NLO activity of these new multipolar chromophores. As previously observed for donor-substituted bipyridine metal complexes [54], the quadratic NLO response increases with the response can be reasonably attributed to an increase in the pdelocalization on the bipyridine ligands induced by the phenyl substituents, a feature that has also been observed in the case of iridium and ruthenium complexes featuring substituted phenanthroline ligands [55,56]. The two-photon absorption cross-sections were measured using either the TPEF (two-photon excited fluorescence) method for fluorescent compounds or using the open aperture Z-scan technique for non emissive ones.…”
Section: Linear Optical Propertiesmentioning
confidence: 55%
“…In recent years, a few reports have appeared in the literature on NLO properties determined by the electric field induced second harmonic generation (EFISH) method and theoretical approaches [16][17][18][19][20]. Notably, Valore et al [21,22] reported that the presence of various charge transfer (CT) processes between the Ir(III) metal center and phenanthrolines ligands also produced a promising NLO response. Meanwhile, inorganic materials have attracted considerable attention as candidates for secondorder NLO materials [23][24][25].…”
Section: Introductionmentioning
confidence: 97%